Analysis of factors affecting the value of property and real estate companies on the Indonesian stock exchange - Etty Harya Ningsi; Irna Triannur Lubis; Lambok Manurung (SEAN Institute, 2024)
This research aims to examine the effect of liquidity and leverage on company value. This research uses a sample of property and real estate companies listed on the Indonesia Stock Exchange in 2020-2022. The research method uses descriptive statistical analysis with a quantitative approach. The data used in this research is secondary data and sampling was carried out using a purposive sampling technique. The number of manufacturing companies in the four years that were the sample for this research was 30 companies. Overall, the sample for this research was 90 financial reports and annual reports. Data analysis techniques use the classic assumption test, multiple linear regression, coefficient of determination, and hypothesis testing (F test and t test). Testing was carried out using the Statistical Product and Service Solution (SPSS) software program. The results of this research show that liquidity affects company value. Leverage has no effect on company value. Simultaneously liquidity and leverage influence company value.